2013
DOI: 10.1002/eji.201242693
|View full text |Cite
|
Sign up to set email alerts
|

Human antibodies reactive to NeuGcGM3 ganglioside have cytotoxic antitumor properties

Abstract: N-glycolylated gangliosides are not naturally expressed in healthy human tissues but are overexpressed in several tumors. We demonstrate the existence of antibodies that bind (N-glycolylneuraminyl)-lactosylceramide (NeuGcGM3) and are detectable in the sera of 65 from the 100 donors (65%) tested by ELISA. From those 65 NeuGcGM3 antibody-positive donors, 35 had antibodies that were able to recognize and kill NeuGcGM3-expressing tumor cells by a complement-mediated mechanism. After complement inactivation, 11 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 50 publications
4
36
1
Order By: Relevance
“…The selective expression of NeuGc-gangliosides in tumors appears to originate from exogenous sources (47,48), and various authors have proposed that tumor hypoxia induces the transcription of a sialin transporter that facilitates the incorporation of NeuGc units into tumor gangliosides (48). Recent reports described the unexpected presence of naturally occurring anti-NeuGcGM3 antibodies, with antitumor potential in healthy donors (39). However, the same team found reduced levels of circulating anti-NeuGcGM3 antibodies in nontreated patients with NSCLC, attributed to the inhibition of the specific antibody-secreting B-cell population, or the formation of immune complexes with the NeuGcGM3 released from tumor cells (39).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The selective expression of NeuGc-gangliosides in tumors appears to originate from exogenous sources (47,48), and various authors have proposed that tumor hypoxia induces the transcription of a sialin transporter that facilitates the incorporation of NeuGc units into tumor gangliosides (48). Recent reports described the unexpected presence of naturally occurring anti-NeuGcGM3 antibodies, with antitumor potential in healthy donors (39). However, the same team found reduced levels of circulating anti-NeuGcGM3 antibodies in nontreated patients with NSCLC, attributed to the inhibition of the specific antibody-secreting B-cell population, or the formation of immune complexes with the NeuGcGM3 released from tumor cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports described the unexpected presence of naturally occurring anti-NeuGcGM3 antibodies, with antitumor potential in healthy donors (39). However, the same team found reduced levels of circulating anti-NeuGcGM3 antibodies in nontreated patients with NSCLC, attributed to the inhibition of the specific antibody-secreting B-cell population, or the formation of immune complexes with the NeuGcGM3 released from tumor cells (39). It has been proposed that idiotypic vaccination is able to boost this natural immune response in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human healthy donors, it was found that naturally occurring antibodies against NeugcgM3 are able to recognize and kill tumor cells expressing this antigen [15] .…”
Section: Introductionmentioning
confidence: 99%